Literasi Keuangan Pasar Modal Bagi Mahasiswa - Anna Nurlita; Aras Aira; Irdayanti Irdayanti; Yessi Nesneri (MENARA RIAU, 2022)
This PKM aims to increase students' knowledge about investing in the capital market, increase the number of investors in Uin Suska Riau, find out what factors influence students' lack of interest in investing in the capital market. PKM was held in the form of a webinar and attended by 39 participants from Uin Suska Riau and Riau University. The results achieved after the PKM implementation were an increase in students' knowledge and understanding of financial literacy in the Capital Market, seen from the number of students' interest in becoming investors in the Capital Market increased after the Webinar was held. The reason for students who have not become Capital Market investors is because they think that being an investor requires large funds and must have a fixed income, besides not understanding stock trading, it is also one of the factors for the lack of interest in investing in the capital market.